The Dynamics of microRNA Transcriptome in Bovine Corpus Luteum during Its Formation, Function, and Regression - Gecaj, Rreze M.; Schanzenbach, Corina I.; Kirchner, Benedikt; Pfaffl, Michael W.; Riedmaier, Irmgard; Tweedie-Cullen, Ry Y.; Berisha, Bajram (Frontiers in Genetics, 2017)
The formation, function and subsequent regression of the ovarian corpus luteum (CL) are dynamic processes that enable ovary cyclical activity. Studies in whole ovary tissue have found microRNAs (miRNAs) to by critical for ovary function. However, relatively little is known about the role of miRNAs in the bovine CL. Utilizing small RNA next-generation sequencing we profiled miRNA transcriptome in bovine CL during the entire physiological estrous cycle, by sampling the CL on days: d 1-2, d 3-4 and d 5-7 (early CL, eCL), d 8-12 (mid CL, mCL), d 13- 16 (late CL, lCL) and d > 18 (regressed CL, rCL). We characterized patterns of miRNAs abundance and identified forty-two miRNAs that were consistent significantly different expressed (DE) in the eCL relative to their expression at each of the analyzed stages (mCL, lCL and rCL). Out of these, bta-miR-210-3p, -2898, -96, -7-5p, -183-5p, -182 and -202 showed drastic up-regulation with a fold-change of ≥ 2.0 and adjusted P <0.01 in the eCL, while bta-miR-146a was downregulated at lCL and rCL versus the eCL. Another 24, 11 and 21 miRNAs were significantly DE only between individual comparisons, eCL versus the mCL, lCL and rCL, respectively. Irrespective of cycle stage two miRNAs, bta-miR-21-5p and bta-miR-143 were identified as the most abundant miRNAs species and show opposing expression abundance. Whilst bta-miR-21-5p peaked in number of reads in the eCL and was significantly downregulated in the mCL and lCL, bta-miR-143 reached its peak in the rCL and is significantly downregulated in the eCL. MiRNAs with significant DE in at least one cycle stage (CL class) were further grouped into eight distinct clusters by the self-organizing tree algorithm (SOTA). Half of the clusters contain miRNAs with low-expression, whilst the other half contain miRNAs with high-expression levels during eCL. Prediction analysis for significantly DE miRNAs resulted in target genes involved with CL formation, functionalization and CL regression. This study is the most comprehensive profiling of miRNA transcriptome in bovine CL covering the entire estrous cycle and provides a compact database for further functional validation and biomarker identification relevant for CL viability and fertility.